Are exporters more environmentally friendly? A re‐appraisal that uses China's micro‐data. (27th September 2020) - Pei, Jiansuo; Sturm, Bodo; Yu, Anqi
Abstract: Is a firm's ability to export an important determinant of environmental performance? To answer this question, we construct a unique microdata set that merged two rich manufacturing firm‐level data sets for China for 2007. When combining this new data set with well‐received empirical specifications, we found that both export status and export intensity are associated with lower sulphur dioxide (SO2 ) emissions intensity. In addition to the traditional OLS estimation, we verified this association by using the propensity score matching method. Our findings show that the baseline result still holds. In short, exporters are more environmentally friendly than nonexporters, which is in line with previous evidence reported for developed economies. We further discuss potential mechanisms that explain the observed pattern and show that exporters realise higher abatement efforts compared to nonexporters. This study complements the literature in terms of providing China's microevidence on SO2 abatement efforts. It also serves as a first step towards a better understanding of the impact of trade on the environment, especially in developing countries.